A Humanistic Phylosophical Analysis on Women Existence in the Fiqh of Syafii - Iffatin Nur (Ulumuna, 2015)
In the fiqh of Shāfi‘ī, a humanistic philosophical analysis on women existence is given serious attention, particularly in his investigation on the matters of women. It is very vivid in his magnum opuses entitled al-Umm (The Mother), al-Risālah fi Us\ūl al-Fiqh and his periodicals qawl qadīm (old view) and qawl jadīd (new view). This article seeks to provide thorough analysis on the women empowerment through humanistic values from methodological and legal products aspects generated by Shāfi‘ī. In the aspect of methodology (us\ūl fiqh), the use of qiyās (analogy) is an indication of the humanistic value in the development of the mas\lah\ah\ (beneficial) principles. The legal products aspect can be explored through the following three classifications. Firstly, humanistic values of women in the law regarding the properties. Secondly, the humanistic values of women in the state law on economic issues related to religious conversion and social relations in political settings. Thirdly, the humanistic values of women in the marriage laws. DOI: http://dx.doi.org/10.20414/ujis.v19i1.1249